Corpus literacy empowerment: taking stock of research to look forward for practice - Li Shuquan; Xu Manfei (Journal of China Computer-Assisted Language Learning)
Over the past decades, corpus linguistics, as an approach to the study of language, has attracted much attention. Applications of its method and various corpus resources have been made in the field of language education as well. However, research in corpus linguistics has not yet been sufficiently converted into a language teacher training perspective especially in the primary and secondary education settings. We therefore call for the development of the corpus literacy of EFL (English as a Foreign Language) teachers as part of their continuous professional development. In support of this call, we examine, from the perspective of a teacher educator, a tentative teacher training model based on the published literature, for student teacher trainees and in-service English practitioners. This paper also offers detailed instructions on how to facilitate the teaching of vocabulary, grammar and discourse with free and user-friendly corpus tools (i.e., SKELL, VersaText and AntConc) in pre-tertiary language classrooms. Some pedagogical implications of the cultivation of EFL teachers’ corpus literacy and major concerns when implementing corpus-based language teaching and learning are also discussed.